Hubungan Health Literacy dengan Self Management pada Pasien Pasca Stroke Iskemik di Klinik Spesialis Saraf RSD dr. Soebandi Jember - Audrey Shafira (Fakultas Keperawatan, 2026)
Post ischemic stroke patients face significant challenges in home-based selfcare, which increases the risk of recurrence and disability. Limited ability to understand and process health information often results in poor self-management skills. This study aimed to identify the relationship between health literacy and selfmanagement among post-ischemic stroke patients at the Neurology Specialist Clinic of dr. Soebandi Regional Hospital, Jember. This study employed a quantitative correlational design with a cross-sectional approach. The researcher selected 84 respondents using purposive sampling based on the G*Power formula. Two validated instruments, the Health Literacy Survey Europe-16 Questions (HLSEU-16Q) and the Southampton Stroke Self-Management Questionnaire (SSSMQ), provided the necessary data. The Spearman’s rho correlation test analyzed the bivariate relationship between variables. The results showed that 50% of respondents possessed a problematic level of health literacy, and 64.3% demonstrated a moderate level of self-management. Statistical analysis revealed a p-value of 0.001 ( < 0.05) with a correlation coefficient (r) of 0.417. The study concludes that a significant relationship between health literacy and selfmanagement in post-ischemic stroke patients at the Neurology Specialist Clinic at dr. Soebandi Regional Hospital in Jember. The correlation between the two variables shows a positive direction with moderate strength, which means that the higher a patient's health literacy level, the higher their self-management ability
FINALISASI oleh Agus 2026 Juni 04
Keywords: Health Literacy; Post Ischemic Stroke; Self Management